Cancer, Health Literacy, and Happiness: Perspectives from Patients under Chemotherapy - Sara Maria Oliveira Pinto; Sílvia Maria Alves Caldeira Berenguer; José Carlos Amado Martins (Nursing Research and Practice)
Cancer is a dreaded disease that affects all dimensions of human life. In this context, issues related to the quality of life—as happiness, perception about health status, or health literacy—are important. This study aims to analyze the following topics the perception: the Portuguese cancer patients have about their health status while undergoing chemotherapy, the satisfaction with the information relating to their health, their level of happiness, and their vision of the future. An observational, cross-sectional, and descriptive study was developed. Data were collected between May and July 2012 in the day hospital of a central hospital in northern Portugal. The sample was composed of 92 cancer patients who were asked to answer a questionnaire during chemotherapy. The results indicate that, despite this life-threatening disease, patients consider themselves fairly happy and have an optimistic view of the future. Information about their health condition and religious beliefs was important coping mechanisms to help dealing with the suffering caused by the disease. The study highlights the importance of providing care in a holistic way. Nurses must be alert and available to listen, answer questions, provide supporting structures, or refer to other professionals when needed.